"Not the only pebble on the beach" - Stenschke, Christoph W. (Neotestamentica, 2011)
Paul's letters to the Corinthians contain many references to other Christians. Paul refers a church of a particular place, the churches of one or several geographical areas and to (all) the churches. He also refers to individual Christians, to "the brothers", "the believers" or "(all)the saints", in an encompassing sense, or of a particular region or of a place. After a complete survey of these references, this article examines their function in Paul's argument. Through these references the Corinthians are reminded that they are "not the only pebble on the beach" but part of a wider community. This status has several implications. For example, the ethical standards of this community also apply to the Corinthians. In addition to ethical issues, Paul's references to his collection for the saints in Jerusalem in 1 Cor 16:1-4 and 2 Cor 8f are particularly telling. These references show Paul's considerable rhetorical skills and aspects of his understanding of the nature and function of the church.